Implicit Meaning And Pragmatic Implicatures InEnglish And Uzbek Political Discourse - Kasimova Nafisa Farkhadovna; Pulatova Mokhidil (Euro Asian Journal Publishing, 2026)
This paper analyzes the pragmatic aspects of political speech in English and Uzbek, with special focus on implicit meaning and pragmatic implicature. The study is based on the pragmatic theory of H. P. Grice, particularly the concept of conversational implicature, and the discourse approach of T. A. van Dijk, which highlights the role of implicit meaning in political persuasion. For the Uzbek linguistic context, the research draws on the ideas of Sh. Safarov, who emphasizes the pragmatic nature of discourse in communication
Keywords: pragmatics; political discourse; pragmatic implicature